Implementation of Problem Based Learning on Physics Learning Outcomes of Students at MAN 1 Makassar - Anwar , Nabilah; Usman, Usman; Nurhayati, Nurhayati; Setiawan, Trisno (Department of Physics Education, Universitas Mataram, 2023)
This research is a pre-experimental study which aims to find out how the visual learning outcomes of MAN 1 Makassar students are described after being taught using problem-based learning with experimental methods. The independent variable of this research is problem-based learning with experimental methods, while the dependent variable is the learning outcomes on the subject matter of harmonic vibrations. The subjects in this study were class X MIPA 1 as an experimental class with 37 students. The research data were obtained by giving a learning achievement test on harmonic vibration material that met valid criteria with 17 questions. The results of the descriptive analysis show that the average score of students who are taught using problem based learning with experimental methods is 13.51 with a standard deviation of 1.95. The category of learning outcomes obtained is in the